2009
DOI: 10.1038/sc.2008.166
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial interference strategy for prevention of UTI in persons practicing intermittent catheterization

Abstract: Study Design Non-randomized pilot trial Objectives Determine whether Escherichia coli 83972-coated urinary catheters in persons with spinal cord injury (SCI) practicing an intermittent catheterization program (ICP) could (1) achieve bladder colonization with this benign organism, and (2) decrease the rate of symptomatic urinary tract infection (UTI). Setting Outpatient SCI clinic in a Veterans Affairs hospital (USA) Methods Participants had neurogenic bladders secondary to SCI, were practicing ICP, had e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 19 publications
3
47
0
Order By: Relevance
“…This can be achieved using catheters that have been preinoculated with nonpathogenic bacteria. 6,36 Small observational trials have shown that patients whose bladders were successfully colonized with the nonpathogenic strains of Escherichia coli had a lower incidence of urinary tract infections than patients with noncolonized bladders. [36][37][38] An RCT compared inoculation of the bladder with a nonpathogenic E. coli 83972 strain to saline in 27 male patients with spinal cord injury.…”
Section: Bacterial Interferencementioning
confidence: 99%
See 1 more Smart Citation
“…This can be achieved using catheters that have been preinoculated with nonpathogenic bacteria. 6,36 Small observational trials have shown that patients whose bladders were successfully colonized with the nonpathogenic strains of Escherichia coli had a lower incidence of urinary tract infections than patients with noncolonized bladders. [36][37][38] An RCT compared inoculation of the bladder with a nonpathogenic E. coli 83972 strain to saline in 27 male patients with spinal cord injury.…”
Section: Bacterial Interferencementioning
confidence: 99%
“…6,36 Small observational trials have shown that patients whose bladders were successfully colonized with the nonpathogenic strains of Escherichia coli had a lower incidence of urinary tract infections than patients with noncolonized bladders. [36][37][38] An RCT compared inoculation of the bladder with a nonpathogenic E. coli 83972 strain to saline in 27 male patients with spinal cord injury. 37 All six participants in the placebo group had at least one urinary tract infection during the one-year follow-up period, compared with 13 of 21 participants (62%) in the experimental group (p = 0.07).…”
Section: Bacterial Interferencementioning
confidence: 99%
“…This could be another factor to consider in the emergence of an increased number of refractory canine UTIs, with a shift towards faecal carriage of less susceptible organisms in some dogs (Mulvey et al, 2000;Johnson et al, 2001a;Prasad et al, 2009). Canine faecal deposits collected from a suburban neighbourhood were shown to contain E. coli strains with similar virulence traits and phylogenetic characteristics to human ExPEC, revealing that dogs may be common reservoirs of these organisms (Johnson et al, 2001a).…”
Section: Observations Of Increasing Antimicrobial Resistance In Straimentioning
confidence: 99%
“…urine collection via cystocentesis, as urine samples collected in this manner are much less often contaminated with commensal bacteria of the skin and urogenital tract and faecal bacteria (Comer and Ling, 1981). Multidrug-resistance is increasingly observed in faecal E. coli (Mulvey et al, 2000;Johnson et al, 2001a;Prasad et al, 2009;Guo et al, 2013) and unintentional isolation of these organisms during the diagnostic workup for UTI may result in overuse of antimicrobials. …”
Section: Epidemiology Of Canine Bacterial Urinary Tract Infectionmentioning
confidence: 99%
See 1 more Smart Citation